(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the development of the compulsory health insurance system in the Russian Federation and analyzes its legal, institutional, and financial mechanisms. The study explores the historical evolution of the Russian healthcare insurance model, the structure of financing, the role of federal and territorial insurance funds, and the implementation of digital healthcare technologies. Particular attention is paid to the challenges and achievements of the Russian model in ensuring universal healthcare coverage. The research findings may serve as a useful reference for healthcare reforms in developing countries, including Uzbekistan.